Toxic stress and protective factors in multi-ethnic school age children: A research protocol - Condon, Eileen M. (Res Nurs Health, 2018)
Exposure to stressful environments in early childhood can cause a toxic stress response and lead to poor health outcomes, including obesity, cardiac disease, diabetes, and mental illness. In animals and maltreated children, the presence of a nurturing caregiver can buffer against the physiological disruptions associated with a toxic stress response; however, the specific caregiver and parenting characteristics that best promote a protective relationship in humans remain largely unexplored, particularly in families living in high-risk environments. In this study, framed in an ecobiodevelopmental (EBD) model, a cross-sectional design is being used to study 54 multi-ethnic, urban maternal-child dyads with children at early school age (4–9 years). Mothers’ past experiences, mental health, and caregiving patterns and children’s hair cortisol, C-reactive protein, pro-inflammatory cytokines, blood pressure, BMI, behavior, and school performance are being analyzed to identify maternal characteristics that may protect against children’s toxic stress response in families at high risk for exposure to stressors such as poverty, trauma, or exposure to violence.